Fuzzy adaptive signal filtering system for arc steel-melting furnace control system - Lozynskyy, Orest; Paranchuk, Yaroslav; Paranchuk, Roman (Видавництво Львівської політехніки, 2011)
A mathematical model of signal fittening for arc steel-melting furnace regimes control system based on fuzzy output system is proposed. Variable model parameters and approaches to the rules base of tuny production system are substantiated.
Keywords: filtering; averaging; fuzzy logic; noise; adaptation